El doctorado de san Josemaría en la Universidad de Madrid / The doctorate of Saint Josemaría at the University of Madrid - Pedro Rodríguez (Studia et Documenta)
The founder of Opus Dei arrived to Madrid in 1927 with the intention of doing his doctoral thesis in Law. The first project he undertook, on the priestly ordination of mestizos and cuarterones during the evangelisation of America, was lost during the Spanish Civil War. The discovery, in the General Archive of the Prelature, of a brief chapter of the draft has allowed for a reconstruction of the different phases of the itinerary of St. Josemaría, so as to arrive to the reading of a new memory of the doctorate, in 1939, regarding the peculiar canonical.